MicroRNA-34a and MicroRNA-181a Mediate Visfatin-Induced Apoptosis and Oxidative Stress via NF-κB Pathway in Human Osteoarthritic Chondrocytes - Sara Cheleschi; Sara Tenti; Nicola Mondanelli; Claudio Corallo; Marcella Barbarino; Stefano Giannotti; Ines Gallo; Antonio Giordano; Antonella Fioravanti (Cells, 2019)
Current evidence suggests a complex interaction between adipokines and microRNA (miRNA) in osteoarthritis (OA) pathogenesis. The present study explored the role of miR-34a and miR-181a in regulating apoptosis and oxidative stress induced by visfatin in human OA chondrocytes. Chondrocytes were transfected with miR-34a and miR-181a inhibitors and stimulated with visfatin for 24 h, in the presence of nuclear factor (NF)-κB inhibitor (BAY-11-7082, 2 h pre-incubation). Apoptosis and reactive oxygen species (ROS) production were detected by cytometry, miRNA, antioxidant enzymes, nuclear factor erythroid (NRF)2 and B-cell lymphoma (BCL)2 expressions by quantitative real time polymerase chain reaction (real time PCR) and western blot. P50 NF-κB subunit was measured by immunofluorescence. Visfatin significantly induced apoptosis and superoxide anion production, increased miR-34a, miR-181a, superoxide dismutase (SOD)-2, catalase (CAT), NRF2 and decreased BCL2 gene and protein expression in OA chondrocytes. All the visfatin-caused effects were suppressed by using miR-34a and miR-181a inhibitors. Pre-incubation with BAY-11-7082 counteracted visfatin-induced expression of miRNA, BCL2, SOD-2, CAT and NRF2. Inhibition of miR-34a and miR-181a significantly reduced the activation of p50 NF-κB. Visfatin confirms its ability to induce apoptosis and oxidative stress in human OA chondrocytes; these effects appeared mediated by miR-34a and miR-181a via NF-κB pathway. We highlight the relevance of visfatin as potential therapeutic target for OA treatment.